Vocational school students’ perceptions toward science learning activities in the context of fashion design - Nur Fadhilah, Dila; Sari, Lasmita; Nurahman, Arip (Insitut Pendidikan Indonesia, 2023)
The structure of the vocational school curriculum is different from the structure of the high school curriculum in that the vocational school curriculum contains vocational subjects which causes students to set aside non-vocational subjects such as science. One of them is science subjects, whose role is unknowingly very important because the learning process prioritizes direct experience and does not become an important concern for students. The purpose of this study was to explore empirical data regarding the perceptions of vocational school students with the expertise of Fashion Design regarding the science learning process. So far, very few or even rare empirical reasons have been found for the perceptions of Vocational High School students of fashion skills regarding the science learning process. This research uses a type of case study research method with a quantitative and qualitative approach. The sampling process in this study used purposive sampling with participants totaling 37 students with an age range of 15-16 years. The instruments used in this study were questionnaires and interviews. The results of the study revealed that there were several different student perceptions in terms of interest, competence, effort, pressure, and values related to science learning activities in fashion design vocational schools.